2013
DOI: 10.1111/nph.12255
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of Kip‐related proteins restrains root‐knot nematode‐feeding site expansion

Abstract: SummaryThe development of nematode feeding sites induced by root-knot nematodes involves the synchronized activation of cell cycle processes such as acytokinetic mitoses and DNA amplification. A number of key cell cycle genes are reported to be critical for nematode feeding site development. However, it remains unknown whether plant cyclin-dependent kinase (CDK) inhibitors such as the Arabidopsis interactor/inhibitor of CDK (ICK)/Kip-related protein (KRP) family are involved in nematode feeding site developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 67 publications
(110 reference statements)
3
75
1
3
Order By: Relevance
“…11,15 Recently, we initiated a detailed functional analyses of the Arabidopsis KRP gene family during RKN [Meloidogyne incognita (Kofoid and White, 1919) Chitwood, 1949] infection, in order to reveal their potential involvement on this plant-pathogen interaction. 16,17 Of the 7 Arabidopsis genes, we observed that 3 members of this family (KRP2, KRP5, and KRP6 ) were highly expressed during at least a certain time span of nematode feeding root-knot nematodes (rKn) are highly specialized, obligatory plant parasites. these animals reprogram root cells to form large, multinucleate, and metabolically active feeding cells (giant cells) that provide a continuous nutrient supply during 3-6 weeks of the nematode's life.…”
Section: How Do Root-knot Nematodes Alter the Host Genetic Program?mentioning
confidence: 99%
See 4 more Smart Citations
“…11,15 Recently, we initiated a detailed functional analyses of the Arabidopsis KRP gene family during RKN [Meloidogyne incognita (Kofoid and White, 1919) Chitwood, 1949] infection, in order to reveal their potential involvement on this plant-pathogen interaction. 16,17 Of the 7 Arabidopsis genes, we observed that 3 members of this family (KRP2, KRP5, and KRP6 ) were highly expressed during at least a certain time span of nematode feeding root-knot nematodes (rKn) are highly specialized, obligatory plant parasites. these animals reprogram root cells to form large, multinucleate, and metabolically active feeding cells (giant cells) that provide a continuous nutrient supply during 3-6 weeks of the nematode's life.…”
Section: How Do Root-knot Nematodes Alter the Host Genetic Program?mentioning
confidence: 99%
“…Despite the accelerated mitotic activity in gall tissues, development of the associated nematodes seems unchanged and these physiological alterations display no synergetic effect to RKN reproduction. 17 …”
Section: How Do Root-knot Nematodes Alter the Host Genetic Program?mentioning
confidence: 99%
See 3 more Smart Citations